NIKAH SIRRI PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Ilham, Muhammad (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
Marriages is a basic right of every body who want to make good and quality family. The term of marriages in nationality or positive law administrative namely marriages registered and unregistered. Today, the marriages unregistered is one of the debatable issues because it assumed illegal marriages. In this paper, writer compared the concept of Islamic and Positive Law toward the Unregistered Marriages. Positively, unregistered marriages is assumed that illegal or not written by Marriage Writer although it become legal based on Islamic Concept. This problem has to concern by every one because it will influence to Kid and Wife’s right. Meanwhile, in Islamic Concept does not know about the Registered Marriages because the marriages is assumed legal if the requirements are fulfilled